Analysis of the expression and function of the CBL-CIPK network and MAPK cascade genes in Kandelia obovata seedlings under cold stress - Tian, Kuo; Li, Qi; Zhang, Xiumei; Guo, Haoyu; Wang, Yihang; Cao, Pinglin; Xu, Shengyong; Li, Weiye (Frontiers in Marine Science, 2023)
Mangroves are an important component of coastal wetland ecosystems, and low temperature is the main factor that limits their extension to higher latitudes. Kandelia obovata as one of the most cold-tolerant species in mangrove ecosystems can provide basis for the northward migration of mangrove ecosystems. We took K. obovata seedlings from Zhoushan (Zhoushan, Zhejiang, China) as the research object in this study. Transcriptome sequencing based on the Illumina HiSeqTM 2500 platform was performed to compare the transcriptome changes of roots, stems, and leaves before and after freezing and to reveal the molecular mechanisms of frost resistance. A total of 1560, 370, and 416 genes were differentially expressed in the roots, stems, and leaves before and after cold snaps, respectively. Among these differentially expressed genes, 13 positive and negative regulators were attributed to the CBL-CIPK signaling network and MAPK cascade, which might be related to the frost resistance mechanism of K. obovata Transcription factors such as AP2/EREBP and bHLH were involved in regulating the synthesis pathways of ethylene, cytokinin, growth hormone, and flavonoids. Results provide new insights into the frost resistance mechanism of K. obovata seedlings.